Religious associations as institutions of civil society: in search of a legal model of interaction with the state - Nikitina, Elena E.; Pomazansky, Andrey E.; Nanba, Saria B. (Journal of the Belarusian State University. Law, 2021)
During the 20th century, most of the intellectual and legal concepts that explain social processes, assigned the church and religion with the role of outdated phenomena of the past, disappearing from the political agenda of modern societies. At the present time an obvious continuity, or even a new wave of religious views and presence of religion in the public sphere have been observed in many countries. Many religious organisations are becoming active actors in public life. Even in official church documents, the church presents itself as an institution of civil society. The article is devoted to reflections on the place of the church and the role of religious associations in the revival of spiritual and ethical principles of civil society in Russia. Since the authors are lawyers, a significant place in the article is devoted to the legislative regulation of the mechanisms and forms of interaction between the state and religious organisations as the significant part of the Russian civil society. Based on the analysis of the current legislation, the authors conclude that at the moment the interaction of religious associations as an integral part of civil society and the state continues to be carried out in outdated and ineffective forms that do not meet the realities of modern life.
Keywords: religion; state; civil society; church; religious organisations; public councils; constitution